Pluralism, the Public Purse, and Education: An International Estimate of Savings to State Budgets from K-12 Catholic Schools - Wodon, Quentin (The review of faith & international affairs, 2019)
According to Church statistics, the Catholic Church has 35 million children enrolled in its primary schools globally, and 20 million children enrolled in its secondary schools. At both levels, enrollment has increased over time globally. While there are debates on whether Catholic schools perform better than public schools, they clearly generate savings for state budgets in many countries since parents choosing these schools often pay for most of the cost of their children's education. This paper estimates budget savings for states from Catholic schools in Organization for Economic Cooperation and Development (OECD) and selected partner countries. In the 38 countries for which estimates are computed, total annual savings are valued at US$ 63 billion in purchasing power parity terms.